The Implementation of Good Governance Principles in Admission of Prospective Civil Servants - Carolina Da Cruz; Sri Kusriyah; Widayati Widayati; Umar Ma'ruf (Jurnal Daulat Hukum, 2022)
The aims of this study are as follows: To analyze and determine the implementation of the principles of good governance in the recruitment of prospective civil servants in Timor Leste and to analyze and determine the factors that influence the implementation of the principles of good governance in the recruitment of prospective civil servants in Timor Leste. The method used by the researcher was a sociological juridical approach and the specifications in this study are descriptive. The results of the research that the implementation of the principles of good governance in the recruitment of prospective civil servants in Timor Leste is wisdom and confidentiality, justice, honesty and integrity, equality, exclusivity regime, conflict of interest, kinshipan integral part of good governance. Factors Affecting the Implementation of Good Governance Principles on the Admission of Candidates for Civil Servants in Timor Leste, as follows: The legal factor itself, namely the entire legislation governing the implementation of Civil Servant Candidate (CPNS/ASN) acceptance. Law enforcement factors, namely people who carry out the law, especially law enforcement officers, in this case are focused on local government officials who are entrusted with the duties and responsibilities by laws and regulations to carry out the selection of CPNS/ASN acceptance. Legal culture factor, namely the habits that apply or are enforced to solve any problems that arise from local government activities in the context of accepting CPNS/ASN. The novelty showed that ability factor of Human Resources (HR), namely the personal circumstances of local government officials who are entrusted with the task of accepting CPNS/ASN and people who submit applications to become CPNS/ASN.